Dental Care Management: Till We Bid Farewell to Covid-19 - Manandhar, Pushkar; Manandhar, Sajana Shrestha (Europasian Journal of Medical Sciences, 2020)
The sudden outbreak of coronavirus disease 2019 (COVID-19) from Wuhan, China shook the whole world. Even though the overall mortality rate of the disease is 3.4% the exponential spread of the virus from China to other parts of the earth got the world into an abnormal global public health crisis. Despite the global effort to control the widespread of the disease, the community spread has been out of hand and declared pandemic with a public health emergency of international concern. The worst is the treatment and vaccine have not been found to date. The Health Professionals have been working day and night on the front line to fight against the virus risking their own life. The oral health professionals, on the other hand, are at the highest risk due to the aerosols produced by saliva droplets. The possibility of the spread of these saliva droplets by inhalation, contamination with skin or mucous membranes, lodgments on the surfaces of the dental offices, or other dental materials used during the dental appointments and/or even the hand contamination could be a big threat to dental professionals. They are in risk not only they get infected but also become a carrier of the virus helping in the spread of it. Thus, this article intends to provide a brief introduction, symptoms and transmission routes of this novel infection along with specific recommendations for oral health practitioners for patient screening and management protocol, and infection control strategies. DOI: https://doi.org/10.46405/ejms.v2i1.48